Long-term effects of imaginal retraining in overweight and obesity: A controlled study. (March 2023) - Gehlenborg, Josefine; Göritz, Anja S.; Moritz, Steffen; Kühn, Simone
Abstract: Background: Imaginal retraining (IR) is a self-help technique that targets automatic approach tendencies toward appetitive stimuli. In a randomized controlled trial (RCT; N = 384), IR reduced craving for high-calorie foods after a six-week intervention period (small effect). The aim of the present study was to evaluate long-term effects of IR in this sample. Methods: One year after baseline, participants from the initial RCT were recontacted. A visual analogue scale measuring craving, the Food Cravings Questionnaire-Trait-reduced (FCQ-T-r), the Three-Factor Eating Questionnaire, the Beck Depression Inventory, quality of life, and subjective appraisal of the intervention were assessed online. Participants were classified as users or nonusers based on self-reported usage of IR over the previous year. Results: Linear-mixed models showed no significant interaction effects of time and group for any outcome (trend level effects were found for two subscales of the FCQ-T-r). Yet, higher usage of IR was associated with greater symptom reduction. Although overall subjective appraisal of the intervention was comparably good to the initial study, usage of IR and completion rate were unsatisfactory. Limitations: Main limitations of the present study include the nonrandomized group allocation and the low completion rate. Conclusions: This study did not find evidence for the long-term efficacy of IR in individuals with craving for high-calorie foods. Only upon high usage of IR, improvement was found. However, low completion rate and usage of the intervention may have resulted in a Type-II error. Future studies may consider low-intensity professional guidance to increase adherence and assess the long-term effects of IR in RCTs. Highlights: We found no significant differences between users and nonusers after one year. Trend effects were found for two subscales of the FCQ-T-r in favor of users. About three quarters of the user sample would recommend the technique. About 60% stated that the intervention reduced their high-calorie eating behavior. Future studies should incorporate professional guidance to increase adherence.